P3.214 Tracking the use and re-emergence of serological techniques for chlamydia trachomatis antibody detection: a systematic review. (8th July 2017) - Migchelsen, Stephanie; Woodhall, Sarah C; Mabey, David; Roberts, Chrissy H
Abstract : Introduction: The presence of antibodies against Chlamydia trachomatis (Ct) is indicative of previous genital or ocular infection. Serology was introduced in the 1970s to support the diagnosis of pelvic inflammatory disease (PID), but fell out of favour due to its cross-reactivity with Chlamydophila ( Chlamydia) pneumoniae bacteria. With the recent development of sensitive and specific assays, as well as the identification of immunogenic Ct antigens developed as recombinant proteins, serology holds the potential to be a useful tool in public health. To date, there has been no summary of the techniques used, their development and their potential usefulness in public and tropical medicine. Methods: We searched PubMed, Cochrane, Lilacs, Scielo, Scopus and Web of Science for articles published on serological techniques and their use in a public health context. Studies were categorised by technique employed, antigen used and antibody detected. Results: A total of 16 studies were included- 5 related to ocular Ct infection and 11 related to genital Ct infection. The trachoma studies were predominantly based on Tanzanian samples, while the genital studies were based on samples from an array of countries. The studies were heterogeneous in design, assay and antigen used, and immunoglobulin detected. The estimated prevalence of antibodies against Ct in trachoma studies ranged from 0%–62%; from 0%–88.9% in genital studies. For genital Ct infections, serology is commonly used to explore disease sequelae. For ocular Ct infections, serology is explored as a means to monitor elimination efforts. Conclusion: Techniques used to measure the prevalence of antibodies against Ct have reported increased sensitivity and specificity. There is wide diversity in antigens and assays used and antibodies detected. The practicality of an assay depends on resources available, purpose of the study, and population being studied. There is wide scope for the development and refinement of techniques to increase the value of serology as it relates to development of new techniques, research and public health.